The legal precedent in online dispute resolution - Carneiro, Davide Rua (2009)
The advances observed in the last years in telecommunication technologies rapidly brought along new ways of doing business. This new reality, however, has not been so rapidly followed by the entities responsible for dealing with the conflicts that arise from these interactions, now undertaken in an electronic format. Traditional paper-based courts, designed for the industrial era, are now outdated. The answer to this problem may rely on the new tools that can be built using new artifacts from fields such as Artificial Intelligence. Using these tools the parties can simulate outcomes, thus having a better notion of the possible consequences of a legal dispute, namely in terms of the Best and Worst Alternative to Negotiated Agreements. In this paper, we present our agent-based architecture for such a tool, UMCourt, placing special emphasis on a particular agent that, based on the concept of legal precedent, gives its users a set of possible outcomes of a case, based on the observation of past similar cases and learns new cases in order to enrich its knowledge base about the Portuguese labor law.